Development and Evaluation of a Sensory Game Teaching Module for Texture Recognition in Early Childhood Education - Riska Aulia Sartika; Ahmad Razak; Rika Kurnia R; Herlina Herlina; Muhammad Akil Musi (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Early childhood learners require developmentally appropriate strategies to support their sensory growth, particularly in recognizing and categorizing textures through direct experiences. This study aimed to develop and evaluate a sensory play-based instructional module designed to enhance texture recognition skills in early childhood learners. Employing a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation), the module was validated by three subject matter experts and implemented in classroom settings. Data were collected through expert validation instruments and teacher assessments to measure its practicality and effectiveness. The module received a validity score of 84.72%, indicating strong content alignment and instructional accuracy. Its practicality was rated at 92.25%, reflecting ease of implementation and contextual relevance, while its effectiveness reached 90.27%, demonstrating improved learner engagement and the ability to distinguish textures through structured sensory activities. These findings confirm the modules high validity, practicality, and effectiveness. Its application offers a valuable instructional strategy for early childhood education by promoting sensory development through evidence-based, play-integrated learning.